Proteases from Latex of Euphorbia spp. and Its Application on Milk Clot Formation - Fibriana, Fidia; Upaichit, Apichat (Biosaintifika: Journal of Biology & Biology Education, 2015)
Crude proteases were extracted from Euphorbiaceae family, i.e. E. milii var imperata, E. trigona, and E. maculata. Among those three crude proteases, the activity of protease from E. trigona was the highest (812.50 U/ml), whereas E. milii and E. maculata crude proteases activity were 298.60 U/ml and 95.80 U/ml, respectively. E. maculata protein concentration was the highest among those three crude enzymes (1.206 mg/ml). The optimum pH and temperature of the enzymes were pH 7.0, pH 6.0, pH 6.5 and 60 C, 50 C, and 50 C, respectively. Crude protease from E. milii var imperata, E. trigona, and E. maculata retained proteolytic activity over a wide range of pH (5.09.0) and temperature (up to 65 C) with casein as substrate. All crude proteases showed milk clotting activity ranged from 0.58 U/ml to 1.01 U/ml. Thus, these crude proteases are potential to be applied in dairy industries. However, further study on enzyme purification and characterization are necessary to obtain high purity of proteases before its application.Protease kasar berhasil diekstrak dari tanaman family Euphorbiaceae, yaitu E. milii var imperata, E. trigona, dan E. maculata. Diantara ketiga protease tersebut, aktivitas protease tertinggi diperoleh dari E. trigona (812,50 U/ml), sedangkan aktivitas protease dari E. milii dan E. maculata adalah 298,60 U/ml dan 95,80 U/ml, berturut-turut. Konsentrasi total protein tertinggi terdapat pada protease kasar E. maculata (1,206 mg/ml). pH dan suhu optimum ketiga enzim tersebut adalah pH 7.0, pH 6.0, pH 6.5 dan suhu 60 C, 50 C, and 50 C, berturut-turut. Protease kasar dari E. milii var imperata, E. trigona, dan E. maculata menunjukkan aktivitas proteolitik pada rentang pH 5.09.0 dan rentang suhu sampai 65 C menggunakan kasein sebagai substrat. Semua protease kasar menunjukkan aktivitas penggumpalan susu dengan rentang dari 0,58 U/ml sampai 1,01 U/ml. Berdasarkan hasil yang diperoleh, protease kasar dari ketiga jenis tanaman ini berpotensi untuk diaplikasikan dalam industri olahan susu. Meskipun demikian, studi lanjut mengenai purifikasi dan karakterisasi sangat diperlukan untuk memperoleh protease murni sebelum aplikasi dalam industri makanan, khususnya pada industri olahan susu.